Formalismo termodinâmico do conjunto irregular para médias de Birkhoff e expoentes de Lyapunov - Silva, Giovane Ferreira (2011)
In this work, we study the set X ̇(φ,f) of points such that the Birkhoff averages do not exist. Following Thompson, our main result here is to show that the topological pressure of X ̇(φ,f) is total. As corollary, we get the some result for the Oseledets Irregular set for Lyapunov exponent in one dimension. For higher dimensions, this question is still open.